2005
DOI: 10.1016/j.febslet.2005.02.068
|View full text |Cite
|
Sign up to set email alerts
|

Plant CULLIN‐based E3s: Phytohormones come first

Abstract: CULLIN (CUL)-dependent ubiquitin ligases form a class of structurally related multi-subunit enzymes that control the rapid and selective degradation of important regulatory proteins involved in cell cycle progression and development, among others. Several classes of these E3s are also conserved in plants and genetic analyses, using Arabidopsis thaliana, indicate that they play an important function during plant development and responses to the environment. In this review, we will discuss the molecular composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 66 publications
0
33
0
Order By: Relevance
“…It has been reported that signal transduction pathways for many plant hormones, including auxin, gibberellin, ethylene, jasmonic acid, and ABA, use ubiquitin-mediated selective protein degradation for their downstream effects (Smalle and Vierstra, 2004). Although there have been several reports about roles of E3 ligases including CRLs in plant hormonal responses, the connection between CRLs and ABA responses is elusive (Thomann et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that signal transduction pathways for many plant hormones, including auxin, gibberellin, ethylene, jasmonic acid, and ABA, use ubiquitin-mediated selective protein degradation for their downstream effects (Smalle and Vierstra, 2004). Although there have been several reports about roles of E3 ligases including CRLs in plant hormonal responses, the connection between CRLs and ABA responses is elusive (Thomann et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant family uses cullins as scaffold proteins to form a framework for assembling the Cullin-RING ubiquitin E3 ligase (CRL), the ubiquitination machinery (Petroski and Deshaies, 2005;Thomann et al, 2005). All cullin family members commonly possess two essential modules assembled on the cullin protein.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to cullin proteins, two other modules are required for the complex: the RING finger protein, RBX1, which recruits E2, and the substrate-recognition module that contains the adaptor and substrate receptor. After all proteins are assembled, the complex acts as an E3 ligase for subsequent target modification (Petroski and Deshaies, 2005;Schwechheimer and Calderon Villalobos, 2004;Thomann et al, 2005) (Fig. 1B).…”
Section: Single-subunit E3 Ligasesmentioning
confidence: 99%
“…Most of the E3 ubiquitin ligases characterised up-to-date act in regulating plant development and hormone signaling [74,75] (Table 2). Notably, an effect frequently observed in E3 ligase Arabidopsis insertional mutants is the arrest of embryo development.…”
Section: Ubiquitin-mediated Degradation: a Re-current Theme In Plant mentioning
confidence: 99%